Hubungan Efek Samping Obat Anti Tuberkulosis (OAT) dengan Kepatuhan Berobat Pada Pasien Tuberkulosis di Puskesmas Jongaya Makassar - Andira, Besse Putri; Dahliah, Dahliah; Wiriansya, Edward Pandu; Irwan, Andi Alamanda; Hamzah, Pratiwi Nasir (Rumah Sakit Ibnu Sina, Makassar, 2024)
Tuberculosis is a direct infectious disease caused by Mycobacterium tuberculosis, which mainly affects the lungs and is transmitted through airborne droplets or sputum from TB patients with positive BTA. The morbidity and mortality of tuberculosis is a serious problem, mainly due to the side effects of Anti-Tuberculosis Drugs (OAT). This study aims to determine the relationship between OAT side effects and treatment compliance of pulmonary tuberculosis patients at the Jongaya Makassar Health Center. This study used a cross-sectional approach with quantitative methods, involving 49 respondents selected using the Slovin formula. The research instruments were OAT side effects questionnaire and treatment compliance questionnaire, with data analysis conducted univariately and bivariately using Chi Square test. The results showed that most respondents experienced low side effects and had a high level of treatment compliance. In conclusion, there is a significant relationship between OAT side effects and treatment compliance of tuberculosis patients at the Jongaya Makassar Health Center, where the lower the perceived side effects, the higher the level of treatment compliance.